Manchas negras dentárias: prevalência e associação com cárie dentária - Pinto, Carolina Camporese França (2011)
The aim of this study was to perform a systematic review of prevalence of black stains and their association with dental caries. Also, this study aimed to estimate the prevalence of dental black stains from a cohort of children born in 2004 in Pelotas, RS, Brazil, evaluating the association with dental caries. For the systematic review, the following electronic databases were accessed: Cochrane Central Register of Controlled Trials, Web of Science, EMBASE, MEDLINE, PubMed, LILACS, BBO. No language restriction was used and the combinations of the following keywords were used: prevalence, black stain teeth, black tooth stain, and their equivalents in Portuguese. The search was limited to studies in children and adolescents with deciduous and permanent teeth, and all studies showing prevalence of black stains were included. The selection of studies was done by three reviewers independently. The cross-sectional study included a sample of 1129 five years old children belonging to the Pelotas birth cohort. Children were visited to carry out examination and a questionnaire including questions about demographics conditions, habits and behaviors related to oral health. Clinical examination included assessment of the presence or absence of black stains and presence of caries by DMFT. Logistic regression was used to analyze the data.The prevalence of black stains was 3.5% (95% CI 2.5 to 4.7), and the prevalence of caries was 48.4% (95% CI 45.4 to 51.4). Black stains and decay were more prevalent in light or dark-skinned black children, in those from mothers with lower level of education and low income level. Adjusted analysis revealed that the presence of black stains was associated with lower levels of dental caries (OR=0.51; 95% CI=0.26-0.99; p=0.048). Considering the results from the systematic review, 129 papers were found from the search with the keywords, and nine met the established inclusion criteria. The prevalence of black stains found in the studies was 10.4% (95% CI 6.8 to 14.1) for permanent teeth, and 4.0% (95% CI 0.43 to 7.5) for deciduous teeth. From the selected studies, five showed lower caries experience in individuals with black stains on the teeth. Conclusions: Based on the analysis of the reviewed studies and considering the data from the cross-sectional study conducted, it is suggested that the diagnosis of black stains should be based on the presence of black spots and / or the formation of linear pigmentation round the gingival margin and / or diffuse the dental crown, and these patches must be difficult to remove, and must be present in at least two teeth. Dark stains can be considered a condition of protection to tooth decay, but studies must be conducted so that the determinant of the black stains and therefore the actual protective factor is known and further explored